PENDAFTARAN SISWA BARU DI SMP NEGERI 9 MUARO JAMBI BERBASIS ANDROID: Based on Android, Mysql, Registration, Design, PHP, New Students. - Pariyadi; Tamrin Syah; Meda, Gustiara (LP2M Universitas Nurdin Hamzah, 2023)
SMP Negeri 9 Muaro Jambi is one of the government agencies engaged in education, in the field of new student registration SMP Negeri 9 Muaro Jambi still uses the manual method, so the author is trying to build a system for designing an Android-based new student registration application, using Php and Mysql, to make it easier users know the recap of registrant data. This study aims to apply information technology to the world of education, especially at SMP Negeri 9 Muaro Jambi and produce an education system that is fast and accurate and makes it easier in terms of student data collection, resulting in the design of Android-based new student registration. This android-based student registration was built using the Android language and MySQL as the database. Android-based student registration at SMP Negeri 9 Muaro Jambi, this is a way to make it easier for the school to input new student data. Android-based student registration at SMP Negeri 9 Muaro Jambi, this can display student personal data information consisting of parental data.